(untitled) - Wertheim-Heck, S. C. O. (Netherlands, 2015)
This thesis addresses consumption as a social practice. The application of social practice based approaches to the analysis of consumption started around the turn of the century and has since gained importance in thinking about food system changes with a strong focus on western developed societies. By applying the research on the specific case of shopping for vegetables in Vietnam, this thesis exemplifies how a social practices approach is relevant beyond OECD countries. In studying the relation and dynamics between local cultural tradition and advanced globalization at the consumption junction, this thesis uncovers how practices of shopping for vegetables and their inherent food safety dynamics emerge, evolve, or die out within the rapidly transforming urban context of Hanoi, Vietnam.
Keywords: Vấn đề an toàn thực phẩm,Food safety issues